Does Higher Openness Cause More Real Exchange Rate Volatility? - Calderón, César; Kubota, Megumi (2012)
The "New Open Economy Macroeconomics" argues that: (a) non-monetary factors have gained importance in explaining exchange rate volatility, and (b) trade and financial openness may have a potential role of mitigating and/or amplifying real and nominal shocks to real exchange rates. The goal of the present paper is to examine the ability of trade and financial openness to exacerbate or mitigate real exchange rate volatility. The authors collected information on the real effective exchange rate, its fundamentals, and (outcome and policy measures of) trade and financial openness for a sample of industrial and developing countries for the period 1975-2005. Using instrumental variables techniques, the analysis finds that: (a) High real exchange rate volatility is the result of highly volatile productivity shocks, and sharp oscillations in monetary and fiscal policy shocks. (b) Countries more integrated with international markets of goods and services tend to display more stable real exchange rate fluctuations. (c) Financial openness seems to amplify the fluctuations in real exchange rates. (d) The composition of trade and capital flows plays a role in explaining the smoothing properties of trade and financial openness. Although the former is mainly driven by manufacturing trade, the latter depends on the share of debt (and equity) in total foreign liabilities. (e) Financial openness would attenuate (magnify) real exchange rate volatility, the greater the share of equity (debt) in foreign liabilities. (f) The composition of flows also matters for explaining the smoothing properties of trade and financial openness in periods of currency crisis.